Twenty Years’ Development of Teacher Identity Research: A Bibliometric Analysis - Zhang, Yunyun; Wang, Ping (Frontiers in Psychology, 2022)
This study aims to demonstrate a detailed knowledge map of teacher identity research via a 20-year data set from the Web of Science (WoS) database. A bibliometric analysis was employed for analyzing the articles published between 2001 and 2021 to show the status of teacher identity research in the past 20 years, research topics on teacher identity, and future research directions. Using the keyword “teacher identity” and filtering data by selecting articles and early access in teaching and education, 848 articles were retrieved. Through production, content, and citation analysis with the help of a bibliometric tool, this study found that teacher identity remained a popular research theme in the academic field over the past 20 years, and its booming production involved many authors, institutions, and sources, and countries. Furthermore, teachers’ “beliefs,” “emotions,” “professional development,” and “context” impacting the construction and reconstruction of teacher identity were the popular topics in teacher identity research, and fundamental issues, including “identity,” “teacher identity,” “professional identity,” “development,” “teacher development,” “beliefs,” and “intersectionality” of teacher identity keep good topics in future research.